2016
DOI: 10.1007/s12274-016-1028-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of riboflavin receptor targeted fluorescent USPIO in mice with prostate cancer xenografts

Abstract: Riboflavin (Rf) receptors bind and translocate Rf and its phosphorylated forms (e.g. flavin mononucleotide, FMN) into cells where they mediate various cellular metabolic pathways. Previously, we showed that FMN-coated ultrasmall superparamagnetic iron oxide (FLUSPIO) nanoparticles are suitable for labeling metabolically active cancer and endothelial cells in vitro. In this study, we focused on the in vivo application of FLUSPIO using prostate cancer xenografts. Size, charge, and chemical composition of FLUSPIO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
3
30
1
2
Order By: Relevance
“…Among the abovementioned indices, the ALT and AST indices are closely related to the liver function of animals, while CREA and BUN levels relate to kidney function. 18 The results revealed that there were no significant differences in any of the indices of the treated rat compared to the untreated rat within an observation period of 3 months, which proved that the DIONs might have no harmful impact on liver and kidney function ( Figure 5D). In order to further evaluate the biosafety, the testing of the blood iron content was performed.…”
Section: Evaluation Of In Vivo Biosafetymentioning
confidence: 83%
See 1 more Smart Citation
“…Among the abovementioned indices, the ALT and AST indices are closely related to the liver function of animals, while CREA and BUN levels relate to kidney function. 18 The results revealed that there were no significant differences in any of the indices of the treated rat compared to the untreated rat within an observation period of 3 months, which proved that the DIONs might have no harmful impact on liver and kidney function ( Figure 5D). In order to further evaluate the biosafety, the testing of the blood iron content was performed.…”
Section: Evaluation Of In Vivo Biosafetymentioning
confidence: 83%
“…They were washed with doubledistilled water 3 times and then observed by fluorescence microscopy (IX-70, Olympus Corporation, Tokyo, Japan). 18 Blue particles in the cell indicated success of staining. Then, we chose the DIONs with an appropriate concentration that had a satisfactory blue staining effect for the following comparison.…”
Section: In Vitro Coincubation Of Lecs and Dionsmentioning
confidence: 99%
“…[23][24][25][26] Thus, a major argument for using RF as a ligand for targeted drug delivery is that it targets both cancerous cells and the tumor stroma including the angiogenic endothelium. 19,27,28 This feature was demonstrated in several preclinical studies with a variety of used carriers -from iron oxide nanoparticles to polymers. 17,18,22,27 In our previous study, we validated the efficacy of cancer and endothelial cell targeting in vitro and in vivo by RF amphiphiles inserted into a liposome formulation.…”
mentioning
confidence: 90%
“…In this context, riboflavin (RF)-based targeting represents a promising approach for cell labeling, 17,18 tumor contrast enhancement, 19 and cell-specific drug delivery. [20][21][22] Due to its involvement in cell growth and development, RF is of high demand in metabolically active cells such as various malignant (eg, breast, prostate cancer, and hepatocellular carcinoma) and rapidly growing endothelial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation